风电齿轮箱行星轮系柔性销轴的强度与疲劳寿命分析 - 李龙; 李剑敏; 陈丽丽; 刘江 (Jixie chuandong)
Taking the flexible pin of planetary gear train in a megawatt wind turbine gearbox as study object,the principle of load equilibration of flexible pin in the muti-planetry gear transmission is analyzed.By using FEA method,the calculation of deformation and the strength checking of flexible pin and sleeve are carried out.Based on the FEA results,using the fatigue life estimation software MSC.fatigue,the fatigue life of the flexible pin and sleeve is estimated and the process of time history loading setup and material S-N curves definition are explained.All the results show that the flexible pin and the sleeve will be safe in the aspects of strength,but in order to meet the durability requirement,it is essential to make some improvements on the shoulder of fexible pin to reduce the stress concentration.